Targeting liver cell metabolism and function in non-alcoholic fatty liver disease - Islam, Tawhidul (2021)
Non-alcoholic fatty liver disease (NAFLD) comprises a series of liver lesions ranging from simple steatosis to non-alcoholic steatohepatitis (NASH) and is a major cause of chronic liver disease that may progress to cirrhosis and hepatocellular carcinoma. Despite the risk factors related with the metabolic syndrome, the mechanisms of disease are not entirely known. Further, several promising molecules with different mechanisms of action are currently in development to treat NASH, although reported efficacy to date has been limited. Therefore, a better understanding of NAFLD pathogenesis and strategies targeting diverse therapeutically responsive nodes should pave the way to find novel and sustainable treatments eagerly waited for disease management. In that regard, we have shown that receptor interacting protein kinase 3 (RIPK3), an indispensable component of necroptosis, is increased in liver samples of human and experimental NASH, resulting in deleterious disease phenotypes including development of hepatic tumorigenesis. Intriguingly, RIPK3 was also found to be a crucial regulator of lipid and mitochondrial energy homeostasis, a role that is yet to be further explored. In turn, as key regulators of hepatic metabolism, farnesoid X receptor (FXR) and G protein-coupled receptor 5 (TGR5) influence NAFLD pathogenesis. In this regard, INT-767, a dual FXR and TGR5 agonist, constitutes a promising therapeutic strategy. Similarly, miR-21 genetic ablation and concomitant use of obeticholic acid (OCA) strongly improved diet-induced NAFLD and NASH through targeting PPARα and FXR, respectively. This further justifies the therapeutic potential of simultaneously activating nuclear receptors and inhibiting miR-21, which points towards multiple targeting approaches that deserve further attention. The main goal of the work presented in this thesis was to elucidate the role of cell death linked to mitochondrial bioenergetic and metabolic function in human and experimental NAFLD and NASH, and to further evaluate the therapeutic relevance of multiple targeting approaches in the resolution of the disease. First, we explored the role of RIPK3 in mitochondrial bioenergetics and hepatic lipid metabolism. Our results showed decreased expression and activities of mitochondrial respiratory chain complexes, downregulation of key mitochondrial biogenesis and function meditators, namely PGC1α, NRF1, NRF2, TFAM and MFN2, as well as increased mitochondrial DNA damage in diet-induced NASH mice. In vitro, murine hepatocytes exposed to palmitic acid (PA) displayed significantly altered mitochondrial morphology, membrane potential and respiration capacity, resulting in higher mitochondrial reactive oxygen species overload. Interestinly, Ripk3 depletion reverted deleterious mitochondrial dysfunction and halted NASH phenotype both in vitro and in vivo. Functional studies in PA exposed cells established a link between RIPK3 and lipid droplet- associated perilipin 1 (PLIN1), which modulated lipid droplet metabolism. This RIPK3-driven altered lipid droplet metabolism was also observed in diet-induced NASH in mice, as well as in a large cohort of human NAFLD patients. We also sought to evaluate the therapeutic potential of FXR and TGR5 dual agonist INT-767 and inhibition of miR-21, alone or in combination, in a pre-clinical model of NASH. INT-767 and anti-miR-21 significantly diminished hepatic lipid accumulation, fibrosis and necroinflammation, while ameliorating lipid and cholesterol homeostasis. Both treatments were effective at improving dysregulated mitochondrial function and halting NASH-associated carcinogenesis, decreasing the formation of pre-neoplastic liver nodules. Noteworthy, the combination of both treatments afforded better protective effects than each strategy alone. Overall, the results of this thesis revealed a key function of RIPK3 in regulating mitochondrial bioenergetics and mitochondria-associated lipid homeostasis in lipid-loaded cells, diet-induced NASH in mice and NAFLD in patients, suggesting RIPK3 as an attractive therapeutic target that deserves further investigation. In addition, simultaneous targeting of more than one therapeutically responsive metabolic nodes of NASH pathogenesis could represent an effective therapeutic approach for better disease resolution. These results highlight the key role of liver cell mitochondrial metabolism in NAFLD and NASH, provide potential therapeutic targets and suggest possible translation into future applications.